Las oportunidades de estudio como incentivo: Los jóvenes de Solidaridad Nacional y la militancia partidaria en el Perú contemporáneo - Ayala Abril, Henry (Pontificia Universidad Católica del Perú, 2016)
Participation through a political party is declining globally (Dalton & Wattenberg 2000). Instead, new, more horizontal forms of politics have emerged which undermine the mobilization capacity of parties (Cross & Young 2008). In Latin America, along with it, informality and the establishment of direct links between the leader and his followers are elements that further weaken the identification with a party organization. Nevertheless, parties persist, surviving from their precarious institutionality and adapting their strategies to obtain a base of militants that support the organization. How to understand this decision of participating in a political party in a context that discourages it?This article discusses the incentives for young people to choose to be militants in a Peruvian personalist party. For this, it studies the case of young people on Solidaridad Nacional party in Lima; an organization that, under the leadership of José Luna Gálvez in 2014, implemented a youth recruitment strategy that adapted the militant supply to the various motivations they had as altruist goals, a political career or opportunities for study or work. Thus, the study highlights the use of Diplomados Solidarios in charge of Telesup University for the recruitment and identification of militants, as well as the importance of altruistic motivations and social norms that attracts young people during the process of political socialization.

La participación a través de un partido político está en declive a nivel global (Dalton y Wattenberg 2000). En su lugar, han surgido nuevas formas de hacer política más horizontales, las cuales merman la capacidad de movilización de los partidos (Cross y Young 2008). En América Latina, junto a ello, la informalidad y el establecimiento de vínculos directos entre el líder y sus seguidores son elementos que debilitan aún más la identificación con una organización partidaria. No obstante, los partidos persisten, sobreviven desde su precaria institucionalidad, y adaptan sus estrategias para obtener una base de militantes que sostenga la organización. ¿Cómo entender esta decisión por participar dentro de un partido político en un contexto que la desincentiva?El presente artículo discute los incentivos por los que los jóvenes deciden militar en un partido personalista peruano. Para ello, se estudia el caso de los jóvenes del Partido Solidaridad Nacional en Lima; organización que, bajo el liderazgo de José Luna Gálvez en 2014, implementó una estrategia de captación de jóvenes que adecuó la oferta militante a las diversas motivaciones que poseían los militantes. Enre ellos, figuraban fines altruistas, el interés en una carrera política u oportunidades de estudio o trabajo. Así, resalta el empleo de Diplomados Solidarios a cargo de la Universidad Telesup para el reclutamiento e identificación de militantes, además de motivaciones altruistas y normas sociales que atraen a los jóvenes durante el proceso de socialización política.
Educational opportunities as an incentive: Solidaridad Nacional’s youth and party membership in contemporary Peru
Keywords: Partidos Políticos; Militancia; Juventud; Solidaridad Nacional; Identificación Partidaria; https://purl.org/pe-repo/ocde/ford#5.06.00